DBU and TU synergistically induced ring-opening polymerization of phosphate esters: a mechanism study. (13th January 2021) - Li, Shuang; Lu, Han; Kang, Xiaohui; Wang, Pan; Luo, Yi
Abstract : Biocompatible and biodegradable polyphosphoesters derived from the ring-opening polymerization (ROP) of phosphate esters have drawn increasing attention because of their potential applications in clinical and therapeutic fields. Abstract : Biocompatible and biodegradable polyphosphoesters derived from the ring-opening polymerization (ROP) of phosphate esters have drawn increasing attention because of their potential applications in clinical and therapeutic fields. The related knowledge of the ROP mechanism, however, is very limited to date. Herein, the ROP of 2-isobutoxy-2-oxo-1, 3, 2-dioxaphospholane (iBP) catalyzed by 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) or the combination of DBU/thiourea (TU, 1-[3, 5-bis(trifluoromethyl)phenyl]-3-cyclohexylthiourea) was computationally studied. It is found that DBU plays the roles of both activating BnOH as an initiator and transporting protons in the two-component DBU/BnOH system. In the three-component (DBU/TU/BnOH) system, two possible mechanisms, viz., DBU- and TU-induced iBP ring-opening, were explored. In the former mechanism, DBU acts as a proton relay and TU is an activator of iBP, whereas protonated DBU serves as a counter cation and TU stabilizes an oxygen-containing anion via hydrogen bond interactions in the latter case. In comparison, the DBU/TU/BnOH cooperatively catalyzed ROP of iBP is more thermodynamically and kinetically favorable than that catalyzed by the two-component DBU/BnOH, which could be mainly ascribed to a more activated P–O bond in iBP by the dual activation role of TU.